Assessing the phylogenetic placement and redundancy of Aspidotheliaceae (Ascomycota), an orphaned family of lichen-forming fungi. Issue 1 (2nd January 2017) - Nelsen, M. P.; Lücking, R.; Cáceres, M.E.S.; Aptroot, A.; Lumbsch, H. T.
Abstract : The lichen-forming fungal genus Aspidothelium has either been considered to represent a separate genus and family or a synonym of Thelenella in Thelenellaceae. At times, a close relationship has been suggested with genera now placed in Celotheliaceae, Monoblastiaceae, Porinaceae, Protothelenellaceae, Pyrenulaceae, Strigulaceae, Thelenellaceae, and Verrucariaceae, families scattered across three ascomycete classes. Consequently, its classification has remained unstable, and the genus is currently listed as incertae sedis within Ascomycota. Here we utilize DNA sequence data to clarify its position. Our sampling suggests that Aspidothelium is embedded within the family Thelenellaceae (Lecanoromycetes: Ostropomycetidae), supporting previous proposals to synonymize Aspidotheliaceae with Thelenellaceae. This clade is allied with the order Ostropales and further work is needed to elucidate whether it should be considered part of Ostropales or a distinct order. Aspidothelium is monophyletic, and its continued recognition requires acceptance of the genus Chromatochlamys . The abandonment of historic classification schemes resulted in the proliferation of many orphaned clades of perithecial, lichen-forming fungi – the present study has clarified the higher-level relationships of one of these enigmatic families, and facilitated its placement in a modern phylogenetic framework.